Formação de professores da educação do campo: uma análise sobre o perfil profissional de docentes da escola estadual Padre José de Anchieta, Serra do Mel – RN - Alves, Ramon Roseno (Universidade Federal Rural do Semi-Árido, 2021)
The present work deals with the central theme of Teacher Education in the final years of Elementary and High School in a school located in a rural context. As a general objective, we seek to analyze the professional profile, in terms of initial and continuing education, of teachers at the Padre José de Anchieta State School, Serra do Mel - RN. With regard to specific objectives, three were considered, namely: (1) to characterize the professional profile, in terms of initial and continuing education, of teachers at the Padre José de Anchieta State School, Serra do Mel - RN; (2) it understands how the formation, initial and continued, of the teachers of the State School Padre José de Anchieta, Serra do Mel - RN, for acting in the context of Rural Education; (3) identify whether there are particularities related to Rural Education in the pedagogical practices of teachers who reside in the community and teachers who reside in the city, from the Padre José de Anchieta State School, Serra do Mel - RN. As for the methodological aspects, it is worth noting that a survey should be carried out considering a qualitative approach, typified as an exploratory and descriptive study, in which the data production technique was a questionnaire consisting of 10 (ten) open questions. The locus of the study was the Padre José de Anchieta State School, located in Vila Brasília, in Serra do Mel/RN. With regard to the subjects of the investigation, fifteen teachers participated, who subdivide the teaching between the final years of Elementary School and High School. In addition to these aspects, we emphasize the reading of the School's Pedagogical Political Project. How to do the work, we point out that most teachers have initial training at a higher level, however, they have not experienced training moments on Rural Education. With regard to continuing education, we noticed that the surveyed teachers demarcate the absence of training actions, from the state education system, which understand them and act contextually in Rural Education. Continuing education is, in most cases, developed as an initiative of the teachers themselves in the areas of knowledge in which they underwent initial training. In general, we identified initiatives in pedagogical practices to contextualize local knowledge along with the curricular contents worked on at school.
Keywords: Educação do campo; Formação de professores; Escola do campo; Profissão professor; Perfil profissional docente; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL